Metode Pembelajaran Multisensori untuk Anak Berkesulitan Belajar Disleksia untuk Meningkatkan Keterampilan Membaca - Larno; Handayani, Arri; Rahmawati, Dini (STKIP Andi Matappa Pangkep, 2024)
Dyslexia is the most common form of learning disability. Dyslexia is not caused by stupidity or mistakes in teaching methods by teachers. They just have difficulties with language, whether it is writing, spelling, reading or counting. This study aims to describe the multisensory method in improving reading skills in dyslexic students. This study uses a qualitative approach with a descriptive method. The purpose of writing this article is to describe the multisensory method that can help improve the reading ability of students with dyslexia in elementary schools. The learning method needed by dyslexic students to help overcome reading difficulties is a method that can function with all the senses to recognize or learn something, namely the multisensory method. With the multisensory method, students learn by utilizing the ability of visual memory (vision), auditory (hearing), kinesthetic (movement), and tactile (touch). The results of the study obtained that the first multisensory method was able to help improve the reading ability of students with dyslexia characteristics in elementary schools, secondly, treatment solutions that could be done to overcome learning difficulties experienced by dyslexic students